1,12-dodecanediol among similar fatty alcohols as a phase change material for thermal energy storage - Ömer Faruk Ensari; Cemil Alkan (Solar Energy Advances)
The majority of research conducted on phase change materials (PCMs) is focused on applicable temperature-based materials. In general, the market offers a limited range of viable alternatives for a number of specific applications. In this study, the 1,12-dodecanediol compound was evaluated as a PCM in its original ambient storage atmosphere. The physicochemical properties of a PCM ultimately determine the conditions under which it can be employed in a given application. Many of these properties, including phase change temperatures, enthalpies, specific heat, and temperature-time relationships, are determined using differential scanning calorimetry (DSC) instruments. In summary, the phase change temperature and enthalpies of 1,12-dodecanediol were found to be 80–76 °C and 238–237 J g⁻¹, respectively, for heating/cooling. Moreover, TGA is used to ascertain the maximum temperature that a common PCM is capable of withstanding. The first degradation temperature of 1,12-dodecanediol (220 °C) was considerable as compared to other organic PCMs. Further thermal analysis of a new PCM may involve thermal conductivity and its potential to increase using conventional additives. The investigation was conducted on 1,12-dodecanediol across the aforementioned aspects. The surface morphology of both the 1,12-dodecanediol and 1,12-dodecanediol/expanded graphite (EG) composites was examined below the phase change temperature using a polarized optical microscope (POM) to reveal surface morphology of 1,12-dodecanediol as the crystalline organic material.